Upland rice yield and soil water retention capacity as affected by cultural practices - Stone, Luis Fernando; Santos, Alberto Baêta dos; Steinmetz, Silvio (Pesquisa Agropecuaria Brasileira, 2014)
Three experiments were carried out to determine the effect of cultural practices on the soil water retention capacity and upland rice yield, using the cultivar ’IAC 47’. The treatments were: a. Subsoiling at 0.60 m depth, spaced 0.50 m; b. Soil harrowing when a hard crust was formed on its surface; c. Liming at 0.30 m depth at the rate of 2.5 t/ha; d. Mulching with rice straw at the rate of 2.5 t/ha and e. Check which was the conventional sowing after the soil tillage with one plowing and two diskings. In the second and third experiments no-tillage treatment was included. Although drought periods (veranicos) occurred, they were not long enough to reduce significantly grain yield. There was no significant difference among the treatments and the check on soil water retention and grain yield. There was tendency of increased production with the treatments of subsoiling and liming and decreased grain yield with the no-tillage treatment. The increase in production due to subsoiling and liming may be related to soil structure modifications and improvement of its chemical properties. The relatively reduced grain yields under no-tillage treatment may be attributed to restricted root development resulting from soil compactness.